Precursor selection for carbon membrane fabrication: a review - Sazali, N.; Wan Salleh, W. N.; Nur Izwanne, M.; Harun, Z.; Kadirgama, K. (Universiti Teknologi Malaysia, 2018)
The rapid expansion of gas separation technology since it was first introduced is promoted by the beneficial selective permeability capability of the polymeric membranes. Up to the currently available information, a large number of studies have reported polymeric membranes permeability and selectivity performances for a different type of gasses. However, trends showed that separation of gases using as per in synthesized polymers had reached a bottlenecks performance limits. Due to this reason, membranes in the form of asymmetric and composite structures is seen as an interesting option of membrane modification to improve the performance and economic value of the membranes alongside with an introduction of new processes to the field. An introduction of new polymers during membrane fabrication leads to a formation of its unique structure depending on the polymers. Thus, structured studies are needed to determine the kinetic behavior of the new addition to membrane structures. This review examines the ongoing progress made in understanding the effects of the different polymers additives to the structural modification and the gas separation performances of the carbon membranes. A reduction of defects consisted of pore holes, and cracks on carbon membranes could be minimized with the right selection of polymer precursor.